Mechanical Properties of Octet Truss and Pyramidal Lattice Cells - Lee, En Hao (2016)
Metal cellular lattice structure is a new class of material that combines useful mechanical properties of metals with customized geometry to provide greater stiffness, strength-to-weight ratio and better energy absorption property. Metal cellular lattice structures are usually made by connecting struts in configurations which determines the kind of deformation they undergo when loaded. Stretch-dominated structures possess higher load bearing capability but lower energy absorption capability than bending-dominated structures. The chosen stretch-dominated structures, pyramidal and octet truss, were designed with varying lattice unit-cell size and relative density in this paper. Unit-cell size and relative density were both varied over three levels – 2 mm, 3 mm and 4 mm, and 20%, 30% and 40% respectively. Total of 4 replicates were created for each combination of design parameters. Physical and mechanical characteristics of the specimens were documented through the use of experiments. Results were then analysed statistically to determine the effects of design parameters have on load bearing capability of specimens. Modulus and yield strength were used as indicators of load bearing capability. This study concludes that topology and relative density influence a specimen’s modulus and yield strength significantly. There is a positive relation between relative density and modulus and yield strength of a specimen. Pyramidal topology offers better load bearing capability than octet truss of the same relative density and cell size.